Knowledge Enhancement about COVID-19 Prevention on Community with Webinar Program - Ratih Damayanti (Universitas Airlangga, 2021)
COVID-19 is increasingly difficult to control. There is evidence of an increase in cases during the beginning of December. There needs to be community participation in prevention and control efforts anywhere (including at home, public facilities and workplaces). Webinars are a method that can be used during a pandemic to increase public knowledge. In this activity, the results showed that some of the participants were female in the age group less than 30 years old with status as students. There was a significant increase in knowledge (p-value = 0.000) of community groups who were provided with counseling through webinars of 9.17 points. It is necessary to expand the reach of people who get counseling through webinars so that information or knowledge about the prevention and handling of COVID-19 can be widely spread throughout Indonesia.